Pengaruh Penggunaan Metode Demonstrasi Terhadap Minat Belajar dan Kemampuan Berpikir Kreatif Siswa Kelas V SD Negeri 005 Palas - Syarifah Aini (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to determine the effect of the use of demonstration methods on the learning interest and creative thinking skills of fifth grade students in science subjects at SD Negeri 005 Palas. This study is motivated by the importance of learning methods to increase students’ active participation and develop creative thinking skills from an early age. The demonstration method was chosen because it allows abstract concepts to be presented concretely and attract students’ attention. This study uses a quantitative approach with a single case study. The subjects of the study were all fifth-grade students of SD Negeri 005 Palas who participated in science learning with the demonstration method. Data collection was carried out using a validated learning interest questionnaire and a creative thinking test. Data analysis was carried out descriptively and quantitatively to describe the level of students’ learning interest and creative thinking skills after being given treatment. The results of the study showed that students showed high learning interest during the demonstration learning process. They seemed more enthusiastic, focused, and actively asked questions during the activity. Furthermore, the results of the creative thinking test showed that students were able to produce original, flexible, and varied ideas. Thus, the use of the demonstration method has a positive influence on students’ learning interest and creative thinking skills in science learning.